FORMS OF CONFLICT: BYRON'S INFLUENCE ON YEATS. (12th April 2015) - Callaghan, Madeleine
Abstract: From Yeats's earliest poetry, Byron looms large in his imagination. It is Byron's poetry of conflict, formal dexterity, political outspokenness, and, most crucially, his poetry of personality that offered a compelling model for Yeats, the aristocratically public poet. This article argues for the significance of Byron's influence on Yeats's poetry. Edward Larrissy and Steven Matthews have suggested the influence of Byron on Yeats, and Yeats himself avows the same to H. J. C. Grierson in a letter. Yet, there has been a relative dearth of studies that focus on their poetic kinship. This article shows that the Yeats–Byron bond, present from Yeats's early to his later poetry, involves a shared double manner, celebratory, and mournful, where both poets fuse sardonic urbanity with imaginative felicity.